Stock assessment of two penaeid prawn species, Penaeus occidentalis and Penaeus stylirostris (Decapoda: Penaeidae), in Golfo de Nicoya, Costa Rica - Tabash B., Farid A (1996)
Analysis on the maturation rate, growth, mortality, selection pattems, recruitment and yield (YIR) and biomass (BIR) per recruitment of P. occidentalis and P. stylirostris in the lower Golfo de Nicoya (Puntarenas, Costa Rica) was undertaken using a length frequency analysis. Results showed that this stock is similar to the one studied in the inner part, as for their maturation and growth parameters. High values of total mortality and exploitation rate were obtained, which indicate that these stocks are overexploited. The analysis of Y/R and B/R showed an overexploited penaeid stock with a very low renewal rateo